FTA Highlight No.8 – Biomass, Bioenergy and Biomaterials - Baral, H.; Sears, R.R.; Brady, M.A.; Meybeck, A.; Gitz, V.; Njenga, M.; Li, Y.; Duguma, L.A.; López, A.; Martius, C. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
The demand for woody biomass for energy and biomaterials is increasing rapidly in line with the global population rise and changing consumption patterns for sustainable resources. Central to meeting this demand is the question of how woody biomass production and use can be reconciled with biodiversity protection, climate change resilience and mitigation, and inclusive prosperity for local communities. Modern, efficient and sustainable forms of bioenergy and biomaterial production and use can play a key role in combating climate change while providing social, economic and environmental benefits to rural communities and critical industries, but these forms are not available to everyone. Thus, attention to social inclusion in the development agendas related to sustainable biomass production, use and trade is vital. Over the last decade, the CGIAR Research Program on Forests, Trees and Agroforestry (FTA) has undertaken basic and applied research on multiple dimensions of woody biomass production and use for energy and materials, such as sustainable production, value chains and investments, enterprise development, and green growth through forest and tree-based circular economies. This highlight discusses the key outputs and findings from FTA work on biomass production and use for bioenergy and biomaterials, in particular woody biomass production in forests and plantations and on farms; the use of biomass; and related value chains. It also considers work on policies that promote sustainability in the sector and discusses the requirements for a shift to a forest- and tree-based bioeconomy.